Citizen Science Helps Uncover the Secrets to a Bat-Friendly Swimming Pool in an Urban Environment - Bennett, Victoria J.; Agpalo, Elizabeth J. (Frontiers in Ecology and Evolution, 2022)
For urban environments to support bat communities, resources need to be readily available. For example, bats typically use urban water sources such as drainage ditches and ponds; however, these sources can be ephemeral. During these periods, bats have utilized residential swimming pools, although they only appear to drink at pools when access to more natural equivalents are limited. This posed the question ‘can we make residential swimming pools friendlier for a diversity of bat species?’. Using citizen science to determine which pool characteristics influenced bat activity, we distributed a questionnaire to residents in a suburban neighborhood in Fort Worth, Texas. It focused on observations of bat activity and the features of the pools and immediate surroundings. We distributed the questionnaire through social media, local presentations, and by mail throughout 2019 and 2020. We then used classification trees to determine which characteristics in combination influenced bat activity at the pools. We generated three different trees for bats observed 1) flying around the property and backyard, 2) above the swimming pool, and 3) drinking at the pool. We found that more bats were observed at unlit pools without bush or shrub borders. Furthermore, among pools with borders, activity was lowest at pools with textured interiors and ≥6 trees visible. The presence of features, such as fountains, then contributed to a reduction in bat observations in backyards and the presence of pets appeared to further reduce activity specifically over the pools. Where bats were observed drinking, this activity was reported the least at pools with bush or shrub borders, textured interiors, and trees <5 m and >10 m from the edge of the pools. Our study revealed that certain characteristics of residential swimming pools encouraged bat activity, while others discouraged them. Thus, it may be possible to make swimming pools more bat-friendly. For example, turning lights off in the evening when backyards are not in use and reducing clutter around pools could have an immediate positive impact on local bat populations. The implementation of such recommendations could improve urban habitats for bats overall and alleviate some of the negative implications of continued urbanization.